Evaluation of the protective effect of chemical additives in the oxidation of phenolic compounds catalysed by peroxidase - Torres, Juliana Arriel; Chagas, Pricila Maria Batista; Silva, Maria Cristina; dos Santos, Custódio Donizete; Corrêa, Angelita Duarte (Environmental technology, 2016)
The use of oxidoredutive enzymes in removing organic pollutants has been the subject of much research. The oxidation of phenolic compounds in the presence of chemical additives has been the focus of this study. In this investigation, the influence of the additives polyethylene glycol and Triton X-100 was evaluated in the phenol oxidation, caffeic acid, chlorogenic acid and total phenolic compounds present in coffee processing wastewater (CPW) at different pH values, performed by turnip peroxidase and peroxidase extracted from soybean seed hulls. The influence of these additives was observed only in the oxidation of phenol and caffeic acid. In the oxidation of other studied phenolic compounds, the percentage of oxidation remained unchanged in the presence of these chemical additives. In the oxidation of CPW in the presence of additives, no change in the oxidation of phenolic compounds was observed. Although several studies show the importance of evaluating the influence of additives on the behaviour of enzymes, this study found a positive response from the economic point of view for the treatment of real wastewater, since the addition of these substances showed no influence on the oxidation of phenolic compounds, which makes the process less costly.